2022
DOI: 10.18280/ijht.400521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Split-Type Air Conditioner Performance under Constant Outdoor Moisture Content and Varied Dry-Bulb Temperature

Abstract: An experimental investigation on the performance of an air conditioner and its operating conditions under constant outdoor moisture content and varied dry-bulb temperature has been accomplished. The test was conducted on an air conditioner using R32 with a nominal cooling capacity of 2.6 kW and the test was carried out in a controlled and standardized test room. During the test, the outdoor temperature was varied from 24 to 36℃ while maintaining the humidity ratio at 14.9 kg vapor per 1 kg of dry air. The indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In comparison to R134a, the DME system has a 4.8% higher COP. The range of COP is in accordance with the results of Setyawan et al [14,15].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In comparison to R134a, the DME system has a 4.8% higher COP. The range of COP is in accordance with the results of Setyawan et al [14,15].…”
Section: Resultssupporting
confidence: 91%
“…The main performance parameters, namely cooling capacity, work of compression, and COP are analysed to determine the overall performance of both refrigerants under different degrees of subcool and superheat. This method has also been used by Setyawan et al [14,15], Mitrakusuma et al [16], and Setyawan [17,18]. Detailed observation of Table 1 reveals that the cooling capacity of the system using R134a increases with the increase of superheating.…”
Section: Methodsmentioning
confidence: 92%
“…They concluded that the highest cooling capacity was obtained at 100% refrigerant charge for all outdoor temperatures, and the cooling capacity dropped by 3.7% as the outdoor temperature increased from 30 °C to 36 °C. Setyawan et al, [18] experimentally investigated the performance of 2.6 kW cooling capacity air conditioner using R32 with outdoor temperature varied from 24 to 36℃ while maintaining the humidity ratio at 14.9 kg vapour per 1 kg of dry air. They concluded that as the outdoor air temperature increased by 1℃, the power input increased by 1.4%, the cooling capacity decreased by 0.9%, and the coefficient of performance decreased by 1.95%.…”
Section: Introductionmentioning
confidence: 99%